2016
DOI: 10.1186/s13104-016-2012-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topically applied Saccharomyces boulardii on the healing of acute porcine wounds: a preliminary study

Abstract: BackgroundNormal wound healing progresses through a series of interdependent physiological events: inflammation, angiogenesis, re-epithelialization, granulation tissue formation and extracellular matrix remodeling. Alterations in this process as well as the bacterial type and load on a wound may alter the wound healing rate. The purpose of this study was to evaluate the effect of topical Saccharomyces boulardii on the healing of acute cutaneous wounds, using a prospective, controlled, experimental study, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In these studies, the mechanism of action was typically not explored, but topical probiotic treatment resulted in improved healing as demonstrated by increased granulation tissue deposition, improved collagen concentration, and stimulation of angiogenesis. [33][34][35][36][37][38][39][40][41][42] However, not all models demonstrated an improvement in topical wound healing with probiotics [33][34][35][36][37][38][39][40][41][42][43][44] (Tables 1 and 2).…”
Section: Wound Healing and Topical Probiotic: General Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the mechanism of action was typically not explored, but topical probiotic treatment resulted in improved healing as demonstrated by increased granulation tissue deposition, improved collagen concentration, and stimulation of angiogenesis. [33][34][35][36][37][38][39][40][41][42] However, not all models demonstrated an improvement in topical wound healing with probiotics [33][34][35][36][37][38][39][40][41][42][43][44] (Tables 1 and 2).…”
Section: Wound Healing and Topical Probiotic: General Studiesmentioning
confidence: 99%
“…They were able to reduce the erythema and oedema associated with CO 2 laser therapy, reduce skin sensitivity in patients with reactive skin, and increase ceramide concentration and skin hydration. [82][83][84][85] However, not all studies investigating topical probiotics have demonstrated superiority compared with traditional interventions 43,44 (Table 2).…”
Section: Wound Healing and Topical Probiotic: Non-pathologicmentioning
confidence: 99%
“…Diametrically opposed the situation in the Germanspeaking and related regions (e.g., Flanders in Belgium): in our German survey, a slight majority (56.1%) was reported to advise their patients against consumption of milk and dairy products [6], with a significant difference between dentists and OMFS in Germany (p = 0.027) (see Table 7), of which those with a focus on surgical procedures attributed at least a minor positive effect on wound [10] Animal model study L. brevis and L. plantarum Decreased inflammation and improved wound healing Jones, 2012 [11] Animal model study L. fermentum Enhanced wound healing Poutahidis, 2013 [12] Animal model study L. reuteri Enhanced wound healing Partlow, 2016 [14] Animal model study S. bouladrii Unimproved wound healing, unchanged microbiome Argenta, 2016 [15] Animal model study L. plantarum Decreased mortality and production of inflammatory markers (TNF-α, IL 6 and 10), less septicemic accumulation in organs Satish, 2017 [16] Animal model study L. plantarum Reduced severity and length of infection and collagen concentration (less scarring) Oryan, 2018 [17] Animal model study S. cerevisiae Enhanced burn wound healing Ong, 2019 [18] Animal model study L. plantarum Enhanced wound healing, suppressed Staphylococcus aureus infection at wound Tagliari, 2019 [19] Animal model study L. paracasei, B. lactis, L. rhamnosus, L. acidophilus…”
Section: Discussionmentioning
confidence: 99%
“…Early identi cation of postoperative skin dysbiosis may then allow for preventive measures to restore a normal skin microbiota. For example, topical probiotic therapy has now been embraced as a method to optimize the skin microbiome 38,39 . Other available interventions to modulate the skin microbiota include topical application of honey-based ointments or the use of enteral probiotics.…”
Section: Discussionmentioning
confidence: 99%